Kesejahteraan Remaja Di Rumah Pangsa: Tumpuan Kepada Penggunaan Ruang untuk Belajar dan Aktiviti Sosial - Yahaya, Nurizan; Mat Nor, Norlela (Penerbit Universiti Sains Malaysia, 1993)
A pilot study was carried out to examine space utilization for study and social activities among adolescents in the flats. The study was carried out at Seri Negeri SembiIan Flat, Bandar Baru Sentul, Kuala Lumpur. The respondents consisted of 80 schooling adolescents i.e. 41 boys and 39 girls aged between 13 to 18 years old. Fourty-nine Malays, six Chinese and 25 Indians adolescents were randomly chosen and interviewed by using questionnaire.